Robust optimal inventory and acquisition effort decisions in a hybrid manufacturing/remanufacturing system. (4th July 2019) - Zhou, Yan-Cong; Sun, Xiao-Chen
ABSTRACT: This paper considers a stochastic multi-period inventory and acquisition effort decisions problem in a hybrid manufacturing/remanufacturing system. Different from past papers, two factors are introduced into the dynamic decision problem. One is the dependency between sales and returns, the other is the dual impacts of acquisition effort on the return of used products and the demand. Few past papers consider them, but they are important and unavoidable for many practical cases. These factors make the problem a high-dimensional decision-making problem, which is difficult to analyze and solve the optimal policy by stochastic dynamic programming, so we employ the robust optimization method. Based on the duality theory, an equivalent robust optimization model is given, which is a convex programming problem. By numerical analyses, we analyze the effects of system parameters on the related decisions and profits, which can provide insights for producers to manage their hybrid manufacturing/remanufacturing systems.